XRCC1 gene variants and possible links with chromosome aberrations and micronucleus in active and passive smokers - Chandirasekar, R.; Suresh, K.; Jayakumar, R.; Venkatesan, R.; Lakshman Kumar, B.; Sasikala, K. (Environmental toxicology and pharmacology, 2011)
► The present investigation was conducted to analyze the genotoxic effects of tobacco on active and passive smokers. ► Three types of genetic test methods were employed including chromosome, micronucleus and XRCC1 arg399gln polymorphism. ► A high level of chromosomal aberrations and micronucleus were observed in active and passive smokers of group III individuals who are exposed to cigarette smoke for more than 41 to 50 years. ► An interesting result was observed that the genotype gln/gln of gene XRCC1 influenced the genotoxic damages in both active and passive smokers. ► This results concludes that both active and passive smoke are at risk of cigarette smoke, moreover the XRCC1 genotype gln/gln specifically involved in influencing the genotoxic effects of tobacco products. Tobacco addiction is a major risk for diseases such as cancers, heart attack, etc. Tobacco smoke constitutes environmental toxins that are the major preventable leading cause of death worldwide. We investigated the influence of tobacco smoke on cytogenetic parameters (chromosomal aberrations and micronuclei) and the influence of XRCC1 arg399gln polymorphism on the cytogenetic parameters of the exposed subjects. The cases for this study include active and passive smokers. They were divided into three groups in accordance with duration of exposure to tobacco smoke. We observed changes in the frequency of chromosomal aberrations and micronuclei among the exposed subjects and controls. Of the three groups of exposed subjects, group III of active smokers and group III of passive smokers showed higher number of chromosomal aberrations and micronuclei when compared to controls, group I and group II of active and passive smokers. The XRCC1 arg399gln polymorphic variant gln/gln, influenced the extent of genotoxic damage in chromosomes and frequency of in micronuclei the three variants (arg/arg, arg/gln and gln/gln), gln/gln harbored significantly ( P < 0.05) higher number of aberrations than the arg/arg and arg/gln. In this context, the results observed in our study indicated that the single nucleotide polymorphism on XRCC1codon 399 influenced the frequencies of chromosomal aberrations and micronuclei.